9 What is the community pharmacist's role in palliative care: views of healthcare professionals within a uk city. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Miller, Elizabeth; Morgan, Julie D; Wong, Christina; Blenkinsopp, Alison
Abstract : Background: Changes in population demographics and greater demand for palliative care are placing increased pressure on general practitioners (GPs) to support patients and families near the end of life. There is little research on how community pharmacists (CPs) contribute and collaborate in the care of palliative care patients in the primary healthcare team. The aim of this study was to determine views of healthcare professionals on the CPs' role in palliative care. Methods: In-depth qualitative semi-structured interviews with a purposive sample of 16 community healthcare professionals. Participants were recruited through e-bulletins, email, team leaders and hospice team within Sheffield. Interviews were audio-recorded, transcribed verbatim and analysed using the Framework method following an inductive and iterative thematic process. Ethical approval was obtained from the University of Bradford. Results: 5 CPs, 3 GPs, 5 community nurses, 2 palliative care team members, and 1 intermediate care team member consented to interview. Two main themes emerged: timely access to palliative medicines and the CP's role in palliative care. There was poor understanding of the CP's professional role and pharmacy services of potential benefit to palliative care patients with nurses and GPs holding a traditional view of CPs in the dispensing and safe supply of medication. The CP's role was limited due to reluctance from other healthcare professionals to share information, poor access to patient records and a lack of integration into the primary healthcare team. Conclusion: Despite the national direction to increase the CPs involvement in palliative care, they remain a largely untapped resource for supporting patients and families towards the end of life due to a lack of integration into primary healthcare teams. Acknowledgements: This research was funded by Pharmacy Research UK (Grant reference GA10). The views expressed are those of the authors and not necessarily those of Pharmacy Research UK.